Method optimization for isolation of Pseudomonas bacteriophage from soil samples - Irteaz, Md. Erfanul Islam (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.